Enzymatic Reduction of Hydrogen Peroxide on Polypogon Australis Plants Grown in a Copper Mining Liquid Waste - Ortiz-Calderon, C; Barros-Vasquez, D (Elsevier B.V., 2017)
This study was undertaken to characterize the status of H2O2-reducing enzyme activity in the metallophyte plant species Polypogon australis when treated with a mining liquid waste (MLW) derived from a copper mine. In order to determine the effect of the solubility of some metals present in the MLW the accumulation of the elements, the variation of H2O2 and lipoperoxidation levels, and their relationship with the H2O2 reduction activity was studied in P. australis plants at pH 5.1 (acidic MLW) and at pH 6.7 (neutral MLW) during two weeks. Plants treated with the acidic MLW showed an elevated copper and zinc accumulation in their tissues. Oxidation of lipids determined by the malondialdehyde (MDA) content increased during the first half hour in the roots of the treated plants, and remained constant to the end of the treatment. In leaves of the treated plants, MDA levels steadily increased throughout the treatment. H2O2 levels increased during the first 2 h of the treatment, then decreased and reached values close to that observed in untreated control plants. The increase of copper in the roots of the plants treated with the acidic MLW and the H2O2 levels detected in the tissues was correlated with the activity of H2O2-reducing enzymes. The results show that the treatment of the plants with the MLW but not the solubility of metals provokes an increase of the H2O2 content in the tissues and triggers the enzymatic control of H2O2 levels. © 2016 SAAB